Depended pH behavior of chitosan on surface modified fibers of Kraft pulp - Noraldin Nazarnezhad (Regional Information Center for Science and Technology (RICeST), 2015)
Chitosan is known as a natural polymer which improves strengths of papers. So, in this study investigated improvement of chitosan absorption on modified craft fibers and increase its efficiency. The effects of chitosan were experimented in three levels of 0%, 0.75% and 1.25% on modified kraft fibers surfaces with 3% hydrogen peroxide in different pH levels (5.5, 7 and 8.5). The results showed that chitosan had better performance at low dosages and alkaline conditions. Also surface fibers modification by hydrogen peroxide caused increase of carboxyl groups and fibers anionic charge. Fibers anionic charge with participant of chitosan formed a dual system. The apparent density increased from acidic pH to alkaline. As, the highest apparent density were reached in alkaline pH and 0.75 % of chitosan. Also, tensile index and burst index of paper were reached in alkaline pH and 0.75 % of chitosan. Whereas, chitosan and the surface modified fibers of kraft pulp did not have a significant level on the tear index